Prediksi employee voice, role clarity, dan performance appraisal terhadap job satisfaction - Riswan Lim Arifin; Rezi Erdiansyah (Universitas Tarumanagara, 2023)
Job satisfaction can protect the health, cause feelings of pleasure, happiness, and increase self-esteem. Satisfaction also affects physical and mental performance, reduces the possibility of employees feeling overloaded, and makes it easier for employees to carry out their duties. Job satisfaction can have a positive effect on employee performance. Researchers managed to collect 64 respondents to collect the required data related to these variables. The results of this study indicate that the results of the t-test for the influence of the employee voice variable show a t-count value of 2.891, the role clarity variable shows a t-count value of 8.371, performance appraisal shows a t-count value of -1.012. The employee voice and role clarity variables show a positive and significant effect on job satisfaction, while the performance appraisal variable has a negative and insignificant effect on job satisfaction. Job satisfaction dapat melindungi kesehatan, menimbulkan perasaan senang, kebahagiaan, dan meningkatkan harga diri. Rasa puas juga memengaruhi performa fisik dan mental, mengurangi kemungkinan karyawan merasakan beban berlebih, dan mempermudah karyawan melaksanakan tugasnya. Job satisfaction dapat berpengaruh positif terhadap kinerja karyawan. Peneliti berhasil mengumpulkan 64 responden untuk mengumpulkan data yang dibutuhkan terkait variabel-variabel tersebut. Hasil penelitian ini menunjukkan bahwa hasil uji t pengaruh variabel employee voice menunjukkan nilai t hitung 2.891, variabel role clarity menunjukkan nilai t hitung 8.371, dan performance appraisal menunjukkan nilai t hitung -1.012. Variabel employee voice dan role clarity menunjukkan berpengaruh positif dan signifikan terhadap job satisfaction, sedangkan variabel performance appraisal berpengaruh negatif dan tidak signifikan terhadap job satisfaction.